Smarce1 fine-tunes cardiomyocyte proliferation in the embryonic zebrafish heart - Park, Deung-Dae; Dahme, Tillman; Krieg, Leonie; Just, Steffen; Rottbauer, Wolfgang (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe molecular mechanisms regulating cardiomyocyte (CM) proliferation during heart development are essential for understanding regenerative processes but remain incompletely defined. While adult mammalian CMs are post-mitotic, zebrafish retain proliferative capacity throughout life. We aimed to identify genetic regulators that fine-tune CM proliferation during cardiac development.MethodsUsing an N-ethyl-N-nitrosourea (ENU) mutagenesis screen in zebrafish, we identified the embryonic-lethal mutant heart of stone (hos), which exhibits cardiac hyperplasia. Genetic mapping revealed a point mutation in smarce1, a component of the SWI/SNF chromatin remodeling complex. We performed morpholino knockdown, mRNA rescue, and Tet-On-driven myocardium-specific overexpression, alongside immunofluorescence, EdU labeling, qPCR, and Western blot analyses.ResultsLoss of smarce1 function in hos mutants and morphants induced ventricular CM hyperproliferation without hypertrophy. Conversely, overexpression of smarce1—both globally and in a myocardium-specific, inducible manner—reduced CM proliferation. Exogenous smarce1 mRNA injection rescued the hyperproliferative phenotype in hos mutants, normalizing CM numbers and mitotic index.DiscussionThese findings identify smarce1 as a cell-autonomous, negative regulator of CM proliferation during zebrafish heart development. Our results highlight the role of SWI/SNF-mediated chromatin remodeling in developmental cardiac growth and suggest that Smarce1 may serve as an epigenetic modulator of cardiogenesis with relevance for future regenerative therapies.